Free Verdict Against Executors of Illegal Fees as Corruption Crimes - Sani, Agnesia Mutiara; Shafira, Maya; Fardiansyah, Ahmad Irzal (Faculty of Law, Universitas Lampung, 2023)
Illegal levies are the designation of all forms of levies that are unofficial, which have no legal basis, so the act of levies is referred to as illegal levies. One of the criminal acts of corruption that occurs in people's lives is illegal fees. An example of a criminal case of illegal fees is the case in Decision Number: 46/Pid.Sus-TPK/2018/PN.Tjk in that case the defendant was acquitted. Judging from the judge's decision that acquitted the defendant, the authors conducted research on the identification of illegal fees as a criminal act of corruption and what was the basis for the considerations of the Panel of Judges in passing an acquittal in cases of criminal acts of corruption based on Decision Number: 46/Pid.Sus-TPK/2018/ PN. Tjk. The problem with this research is the identification of extortion as a criminal act of corruption. and what are the basic considerations of the Panel of Judges in passing an acquittal in a corruption case based on Decision Number: 46/ Pid.Sus -TPK/2018/PN. Tjk The research method used is normative juridical research method, sources of primary and secondary legal materials. From this study it can be concluded that illegal fees can be categorized as a criminal act of corruption, this action is regulated in Article 12 letter e of Law Number 31 of 1999 which has been amended and added to Law Number 20 of 2001 concerning Eradication of Corruption Crimes. That the basis for the judge's considerations in deciding that the corruption case was free of Decision Number: 46/Pid.Sus-TPK/2018/PN.Tjk Defendant did not meet the elements of